(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article analyzes the educational and cultural reforms implemented in New Uzbekistan and their role in society. Also, the article highlights the practical proposals put forward by Uzbekistan in order to improve the cultural life of the world community and the issue of the country’s cultural relations with UNSESCO.